Professors, Physicians and Practices in the History of Medicine
XVI, 307 p. 28 illus.
Keywords: This book presents essays by eminent scholars from across the history of medicine, early science and European history, including those expert on the history of the book. The volume honors Professor Nancy Siraisi and reflects the impact that Siraisi's scholarship has had on a range of fields. Contributions address several topics ranging from the medical provenance of biblical commentary to the early modern emergence of pathological medicine. Along the way, readers may learn of the purchasing habits of physician-book collectors, the writing of history and the development of natural history. Modeling the interdisciplinary approaches championed by Siraisi, this volume attests to the enduring value of her scholarship while also highlighting critical areas of future research. Those with an interest in the history of science, the history of medicine and all related fields will find this work a stimulating and rewarding read.